2022
DOI: 10.30651/st.v15i2.13379
|View full text |Cite
|
Sign up to set email alerts
|

Kemampuan Berpikir Kritis Siswa Melalui Analisis Sastra

Abstract: Student Critical Thinking Skills Through Literary Analysis ABSTRAKMelalui analisis sastra, siswa dapat memperoleh keterampilan berpikir kritis. Sastra merupakan salah satu cabang seni yang mengalami proses pertumbuhan sejalan dengan perjalanan waktu dan perkembangan pikiran masyarakat. Literatur dalam proses belajar mengajar dapat menciptakan keterampilan berpikir kritis. Siswa akan berlatih mengungkapkan pendapat, menyimpulkan, menjelaskan hubungan sebab-akibat, membandingkan fakta, dan menerapkan ide-ide yan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The analysis was conducted by examining the overall average score of each aspect, starting from the highest to the lowest. According to Santoso in Ramadhana et al (2022), to understand the pattern of answers and phenomena observed from respondents, a percentage analysis was carried out using a certain formula. The percentage formula used is as follows: The criteria and percentage score of the Arabic morphosemantic ability test answers can be seen in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis was conducted by examining the overall average score of each aspect, starting from the highest to the lowest. According to Santoso in Ramadhana et al (2022), to understand the pattern of answers and phenomena observed from respondents, a percentage analysis was carried out using a certain formula. The percentage formula used is as follows: The criteria and percentage score of the Arabic morphosemantic ability test answers can be seen in Table 1.…”
Section: Methodsmentioning
confidence: 99%